2009
DOI: 10.2478/v10007-009-0025-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drug solubility on the release kinetics of water soluble and insoluble drugs from HPMC based matrix formulations

Abstract: Effects of drug solubility on the release kinetics of water soluble and insoluble drugs from HPMC based matrix formulations The purpose of the present research work was to observe the effects of drug solubility on their release kinetics of water soluble verpamil hydrochloride and insoluble aceclofenac from hydrophilic polymer based matrix formulations. Matrix formulations were prepared by the direct compression method. The formulations were evaluated for various physical parameters. Along with the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
3
17
0
1
Order By: Relevance
“…Table III summarizes the calculated release parameters applying different models as zero‐order, first‐order, and Korsmeyer–Peppas 46. All data fit very well with Korsmeyer–Peppas model by R 2 ≥ 0.995, which confirms the release kinetics of a water‐insoluble drug 47. In the Korsmeyer–Peppas model, when the release exponent n = 0.43, it theoretically indicates a diffusion‐controlled mode, while n = 0.85 indicates a swelling‐controlled mode 46.…”
Section: Resultssupporting
confidence: 58%
“…Table III summarizes the calculated release parameters applying different models as zero‐order, first‐order, and Korsmeyer–Peppas 46. All data fit very well with Korsmeyer–Peppas model by R 2 ≥ 0.995, which confirms the release kinetics of a water‐insoluble drug 47. In the Korsmeyer–Peppas model, when the release exponent n = 0.43, it theoretically indicates a diffusion‐controlled mode, while n = 0.85 indicates a swelling‐controlled mode 46.…”
Section: Resultssupporting
confidence: 58%
“…Chakraborty et al has explained that the release kinetics of a water-insoluble drug such as verapamil from HPMC based formulations follows Korsmeyer-Peppas model. It means that drug release occurred through diffusion in the hydrated matrix and polymer relaxation [65]. So it can be acceptable for water-insoluble paclitaxel too.…”
Section: In Vitro Drug Releasementioning
confidence: 98%
“…However, many researchers involved in the development of the PPN sustained-release dosage forms met with problems, such as difficulty in the control of drug release due to the high aqueous solubility of PPN. These challenges led to the use of a large amount of polymer in the matrix tablets to support the sustained release of a drug with high water solubility[14]. Recently, it was shown that PPN could electrostatically interact with MAS to form intercalated complexes.…”
mentioning
confidence: 99%
“…Hydroxypropylmethylcellulose (HPMC) has been widely used as a hydrophilic matrix forming agent[1417] and was employed in this study. Additionally, the effects of HPMC viscosity grades, compression pressures and calcium acetate incorporation on the PPN release characteristics of the PPN–MAS complex tablets were also examined.…”
mentioning
confidence: 99%